Adaptive modulation and regenerator-aware dynamic routing algorithm in elastic optical networks - Aibin, Michal; Walkowiak, Krzysztof (2015 IEEE International Conference on Communications (ICC), 2015)
Elastic optical network (EON) is a promising technology that provides flexible modulation format conversion, which allows more efficient use of spectrum resources comparing to classical fix-grid in WDM networks. In addition, a significant issue observed currently is the predominant role of cloud computing and content-oriented services provided by geographically dispersed data centers. Consequently, an anycast transmission - defined as one-to-one-of-many - gains much attention due to the need for cost-effective and scalable data delivery in inter-data center networks. In this paper, we address the Routing, Modulation and Spectrum Allocation (RMSA) problem in the context of dynamic routing for anycast and unicast traffic in EONs. We propose a new adaptive and regenerator-aware algorithm for dynamic RMSA that facilitates the possibility of modulation change along the lightpath. Numerical experiments clearly show advantage of our approach comparing to previous methods in terms of blocking probability. Moreover, our results show an interesting trade-off between blocking probability and the usage of regenerators.